(untitled) (SAARC Journal of Agriculture, 2024)
An experiment was conducted at the farmer’s field of Dacope upazila under Khulna district during the two consecutive rabi seasons of 2019-20 and 2020-21 to find out the effect of plant spacing and variety on yield and quality of maize in coastal region. The experiment comprised two set of treatments viz., (a) Plant spacing: 60 cm x 20 cm (S1); 55 cm x 20 cm (S2); 50 cm x 20 cm (S3) and 45 cm x 20 cm (S4) and variety (b) BARI hybrid Maize-16 (V1); Sunshine (V2) and NK 40 (V3) in split plot design (where plant spacing in the main plot and variety in the sub plot) with three replications. The results showed that the variety Sunshine planted with 60 cm × 20 cm plant spacing (S1V2) produced significantly the tallest plant and maximum number of leaves plant-1. BARI hybrid Maize-16 planted with 60 cm × 20 cm plant spacing (S1V1) showed significantly the highest yield attributes and carbohydrate content. NK 40 planted with 60 cm × 20 cm plant spacing (S1V3) produced significantly the maximum protein content. But the treatment combination S4V1 (BARI hybrid Maize-16 with planted with 45 cm × 20 cm plant spacing) produced significantly the highest grain yield (8.43 t ha-1) due to higher number of plant population. SAARC J. Agric., 22(1): 191-202 (2024)